A study on the use of authentic materials in reaing instruction for first year mainstream students at felte-ULIS-VNU = nghiên cứu việc sử dụng tài liệu thực tế trong việc dạy đọc cho sinh viên năm nhất hệ đại trà khoa Sư phạm tiếng Anh - Lưu, Trà Giang (2020)
Under the communicative approach, authentic materials have gradually been integrated into reading courses for first-year students studying in Faculty of Language Teacher Education (FELTE) in University of Languages and International Studies (ULIS). The effectiveness of using authentic materials depends crucially on how teachers select and exploit them for reading activities. Although in the scope of ULIS, VNU, some research related to the use of authentic materials has been conducted, there has not been any research investigating into reading instruction for FELTE students. To fill in this gap, “A study on the use of authentic materials in reading instruction for first-year mainstream students at FELTE-ULIS-VNU” was conducted. The participants were 104 freshmen and 12 teachers of reading courses from FELTE, ULIS. Three instruments namely questionnaire for students, semi-structured interview and observation were employed to collect data which were analyzed by qualitative and quantitative methods. The results showed that all of the teachers had positive attitudes toward the use of authentic materials in their reading classes; however, they held neutral views when comparison between authentic materials and textbooks was made. Therefore, all of them approved of the use of both kinds in reading instruction. When using authentic materials, asking students’ experiences was the most popular technique in pre-reading stage; skimming and extensive reading were more focused in while-reading; and discussion was frequently hold at the end of classes, which underlines the interactive model of reading process. The students were generally motivated by the reading activities based on authentic materials. Furthermore, they were considerably motivated to learn reading and to do more reading outside the classroom.